Energy Hub Conceptual Improvement with Household Involvement (CONECT. International Scientific Conference of Environmental and Climate Technologies, 2026)
Existing energy systems in the global energy market are often based on the centralized generation using fossil fuels, which has been increased due to the high impact of lobbyists in fossil resource market and geopolitical situation. However, due to the increased renewable energy resource implementation in the energy portfolio, shift to more decentralized energy production and distribution is increased and supported. Energy hubs and demand response programs has been increasingly studied for energy sector adaptation and implementation, which allows to adapt demand to the supply, which is relatively fluctuating due to discontinuity of the solar and wind energy. Most recent reviews regarding energy hubs and energy sector are general are highlighting the various solutions for energy supply balancing, which include residential and industrial sector involvement into the demand response program, using household appliances, electric vehicles and other shiftable electricity consumers. Other demands in energy hub are crucial for optimal distribution of energy in the energy hub, like heat, natural gas and domestic water. Energy management in energy hub is organized by aggregators, which are responsible for most optimal distribution, storage and price of electricity, prioritizing locally generated power over imported electricity from centralized units. Such approach allows to exploit he locational value of energy and bypass the transfer losses via conventional distribution network. Such losses are more impactful during the peak hours, which increases the electrical load of the wire, thus increasing the marginal losses. High importance is social approval of energy system development to energy hubs, thus involving consumers more, than some might be interested in, thus survey will be conducted to determine the opinion and limitations of society in Latvia. Aim of this research is to improve the energy hub concept modeling and social aspects and meanwhile address the main problematics of the currently developed systems, especially based on household involvement and sizing restrictions.